2003
DOI: 10.1130/b25314.1
|View full text |Cite
|
Sign up to set email alerts
|

Timing and style of Late Quaternary glaciation in northeastern Tibet

Abstract: Glacial successions in the Anyemaqen and Nianbaoyeze Mountains of northeastern Tibet are reassessed and new glacial chronologies are presented for these regions. Cosmogenic radionuclide and optically stimulated luminescence dating indicates that two glacial advances occurred in marine isotope stage (MIS)-3 and MIS-2. In the Anyemaqen Mountains, a third advance occurred in the Early Holocene. We suggest that glaciation was synchronous in the Anyemaqen and Nianbaoyeze Mountains, as well as in other glaciated are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 156 publications
(104 citation statements)
references
References 46 publications
(61 reference statements)
7
91
1
5
Order By: Relevance
“…The glacial advances would have still dated to the early Holocene, Lateglacial and MIS 3 regardless of the scaling model used to calculate the ages. This indicates and supports the view of Owen et al (2003a) that glaciers in this region are influenced by the South Asian monsoon. The maximum extent of glaciation occurred early in the last glacial cycle (MIS 3) during a time of increased insolation when the monsoon was intensified and supplied abundant precipitation, as snow at high altitude, to feed highaltitude glaciers.…”
Section: Key Areassupporting
confidence: 76%
See 3 more Smart Citations
“…The glacial advances would have still dated to the early Holocene, Lateglacial and MIS 3 regardless of the scaling model used to calculate the ages. This indicates and supports the view of Owen et al (2003a) that glaciers in this region are influenced by the South Asian monsoon. The maximum extent of glaciation occurred early in the last glacial cycle (MIS 3) during a time of increased insolation when the monsoon was intensified and supplied abundant precipitation, as snow at high altitude, to feed highaltitude glaciers.…”
Section: Key Areassupporting
confidence: 76%
“…This was disputed by many and it stimulated much research in Tibet, especially as China began to open its borders to western scientists and strengthened its international research collaborations. Over the past few decades, numerous publications have presented the evidence against an extensive ice sheet (Derbyshire, 1987;Zheng, 1989;Shi, 1992;Hö vermann et al, 1993a,b;Lehmkuhl, 1995Lehmkuhl, , 1998Rutter, 1995;Lehmkuhl et al, 1998;Zheng and Rutter, 1998;Schäfer et al, 2002;Owen et al, 2003a). Now it is generally accepted that a large ice sheet did not cover the Tibetan Plateau, at least not during the past few glacial cycles.…”
Section: Extent Of Glaciationmentioning
confidence: 99%
See 2 more Smart Citations
“…A cold, dry climate was also recorded during MIS2 based on the decline of pollen concentration and the deposition of halite in the core sediment. Previous studies on Pleistocene glaciers demonstrated that a Late Pleistocene glacier in northeastern TP advanced during MIS3b and MIS2 (Owen et al, 2003;Owen et al, 2006;Ou et al, 2014). Meanwhile, the mean moisture values decrease noticeably in central Asia after 2.7 ka BP (Herzschuh, 2006).…”
Section: Regional Correlation and Possible Mechanismmentioning
confidence: 99%